2018
DOI: 10.1021/jacs.8b11793
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic, Enantioselective Synthesis of Cyclic Carbamates from Dialkyl Amines by CO2-Capture: Discovery, Development, and Mechanism

Abstract: Cyclic carbamates are a common feature of small molecule therapeutics, offering a constrained hydrogen bond acceptor that is both polar and sterically small. Methods for their preparation most often focus first on aminoalcohol synthesis and then reaction with phosgene or its equivalent. This report describes an enantioselective synthesis of cyclic carbamates in which carbon dioxide engages an unsaturated basic amine, facilitated by a bifunctional organocatalyst designed to stabilize a carbamic acid intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 86 publications
(49 reference statements)
0
33
0
Order By: Relevance
“…NHAr Cl R (1) HCl R (1) NHAr O R (1) O N N Bu Cl H N O R (1) R (1) Ar These last two reactions have been employed also for larger cyclic carbamates than oxazolidinones. Very recently, an enantioselective cyclization was developed to prepare six-membered cyclic carbamates from homoallylic amines (Scheme 25) [182]. The catalyst was studied in order to have Brønsted basicity enough to avoid amine to form an achiral carbamate salt intermediate.…”
Section: Scheme 13mentioning
confidence: 99%
“…NHAr Cl R (1) HCl R (1) NHAr O R (1) O N N Bu Cl H N O R (1) R (1) Ar These last two reactions have been employed also for larger cyclic carbamates than oxazolidinones. Very recently, an enantioselective cyclization was developed to prepare six-membered cyclic carbamates from homoallylic amines (Scheme 25) [182]. The catalyst was studied in order to have Brønsted basicity enough to avoid amine to form an achiral carbamate salt intermediate.…”
Section: Scheme 13mentioning
confidence: 99%
“…All of the reported methods require the use of a catalyst unless high CO 2 pressure or supercritical carbon dioxide is employed . Thus, unsaturated amines, haloamines, and amino‐alcohols have been investigated for their cyclization reactions with CO 2 to afford 2‐oxazolidinones; even three‐component systems may be effective, and in this regard, several epoxide/amine, alkyne/amine, and alkene/amine combinations have been considered. Repo and co‐workers demonstrated that a series of N ‐aryl‐2‐oxazolidinones are accessible from the one‐pot carboxylation of aniline/1,2‐dibromoethane in organic solvents under mild conditions .…”
Section: Introductionmentioning
confidence: 99%
“…While additional spectral information concerning the acid's diffusion coefficient is lost, the deduction proved robust and suggested a 1:1 complex between the Brønsted acid and substrate base. This methodology has subsequently been successfully used in a number of fields, particularly by Day and Weaver to help confirm their successful synthesis of 2,3,5,6-tetrafluoro-4-(nitromethyl)pyridine [155] and by Yousefi et al to confirm the stoichiometry of complexes formed during carbon dioxide capture/cyclization reactions performed using chiral Brønsted acid catalysts [156].…”
Section: Fmentioning
confidence: 98%